Jose P. Rizal : a hero's life - Tabotabo, Claudio V.; Leano, Roman D. Jr. (Manila, Philippines : Mindshapers Co. Inc., 2009)
This book traces the heroism of Rizal. It identifies the inner qualities of the hero that influenced his life from boyhood in Calamba to the fateful morning at Bagumbayan.
Chapter 1 Jose and the Rizal family -- Chapter 2 Rizal as lover -- Chapter 3 Philosophy of Rizal -- Chapter 4 The novel and some poems of Rizal -- Chapter 5 Peaceful life in Dapitan -- Chapter 6 The martyrdom of Jose Rizal.
Includes bibliographical references.
Keywords: RIZAL, JOSE, 1861-1896